Karakterisasi Kinerja Formulasi Lost Circulation Material terhadap Efisiensi Pembentukan Impermeabel Barrier pada Kondisi Peningkatan Tekanan Diferensial - Limbong, Samuel Sampe Tua Sauduran; Rahman, Muhammad Rizqie Fathan; Fitria, Debby Nur (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Lost circulation in large-fracture formations is often driven by the inability of Loss Circulation Material (LCM) to maintain a stable barrier under increasing differential pressure. This study evaluates the effectiveness of various LCM formulations in forming and sustaining impermeable barriers within a 3000-micron slot. Secondary laboratory data from slotted disk tests at 200, 300, and 500 psi were analyzed using an ordinal scoring method to quantify performance. Results show that most formulations successfully create initial bridging at 200 psi; however, only multimodal combinations of granular (CaCO₃) and fibrous materials sustain sealing up to 500 psi. Blended organic cellulose fiber (BOCF) demonstrates superior performance compared to microcellulose fiber (MCF) due to better elasticity and particle interlocking. The findings indicate that LCM effectiveness depends on material synergy and particle size distribution rather than initial bridging alone. It is recommended to apply multimodal granular–fibrous formulations for severe loss conditions in large fractures.